Expression profiling suggests microglial impairment in human immunodeficiency virus neuropathogenesis. Issue 2 (10th February 2018) - Ginsberg, Stephen D.; Alldred, Melissa J.; Gunnam, Satya M.; Schiroli, Consuelo; Lee, Sang Han; Morgello, Susan; Fischer, Tracy
Abstract : Objective: CD16 + /CD163 + macrophages (MΦs) and microglia accumulate in the brains of patients with human immunodeficiency virus (HIV) encephalitis (HIVE), a neuropathological correlate of the most severe form of HIV‐associated neurocognitive disorders, HIV‐associated dementia. Recently, we found that some parenchymal microglia in brain of HIV + subjects without encephalitis (HIV/noE) but with varying degrees of neurocognitive impairment express CD16 and CD163, even in the absence of detectable virus production. To further our understanding of microglial activation in HIV, we investigated expression of specific genes by profiling parenchymal microglia from archival brain tissue of patients with HIVE and HIV/noE, and HIV − controls. Methods: Single‐population microarray analyses were performed on ∼2, 500 laser capture microdissected CD163 +, CD16 +, or CD68 + MΦs/microglia per case, using terminal continuation RNA amplification and a custom‐designed array platform. Results: Several classes of microglial transcripts in HIVE and HIV/noE were altered, relative to HIV − subjects, including factors related to cell stress, immune activation, and apoptosis. Additionally, several neurotrophic factors were reduced in HIV infection, suggesting an additional mechanism of neuropathogenesis. The majority of transcripts altered in HIVE displayed intermediate changes in HIV/noE. Interpretation: Our results support the notion that microglia contribute to the maintenance of brain homeostasis and their potential loss of function in the context of chronic inflammation contributes to neuropathogenesis. Furthermore, they indicate the utility of profiling MΦs/microglia to increase our understanding of microglia function, as well as to ascertain alterations in specific pathways, genes, and potentially, encoded proteins that may be amenable to targeted treatment modalities in diseases affecting the brain. Ann Neurol 2018;83:406–417